Oral health impact on quality of life assessment among dental patients in Bangalore city - Y Pradeep; K Pushpanjali (Wolters Kluwer Medknow Publications, 2014)
Introduction: Over the past few decades mankind has been mainly affected with chronic noncommunicable diseases, which led to compromised quality of life. Common dental diseases come under same categories that are largely social and behavioral in origin. Health-related quality of life helps us address the limitations of traditional clinical indicators of health. Aim: To measure the impact of oral health on quality of life among patients visiting dental teaching hospitals and private clinics in Bangalore city using oral health-related quality of life (OHQoL) - U.K index. Materials and Methods: A total of 1200 individuals who are above 16-year of age were selected through stratified cluster random sampling technique for this study. Data were collected using OHQoL-U.K instrument. Results: Most of the subjects (78%) perceived their oral health as impacting their quality of life. Many participants perceived their oral health had positive impact on life quality through enhancing their smile, appearance, speech. But 44.9% and 28.5% of respondents said their oral health has a negative impact on quality of life because of breath odor and finance respectively. Subjects are belonging to lower socioeconomic background, women and older adults (>45 years) perceived their oral health has a negative impact on quality of life compared to subjects from higher social class, men and young adults. Conclusion: Oral health has more impact on physical and functional aspects rather than on social and psychological domains.